Musicorum Collegio: Fourteenth-Century Musicians' Motets - Harrison, Frank Llewellyn (Monaco Éditions de l'Oiseau-Lyre, 1986)
Pref. in English and French.Reprinted from v.5 and v.15 of the series Polyphonic music of the fourteenth century.Latin words also printed as text, p. 36-38, with English translation or synopsis.For 3-5 voices, unacc.
Keywords: Middle Ages (500-1400); Motet; Musician; Biography